Study On Knowledge and Practice of Islamic Lifestyle Towards Hypertension Among Coworkers At Kolej Permata Insan: A Preliminary Study - Nur Farisya Sara Saiful Hasmerol Erwan; Adriana Khairin Khairuddin; Nurdalila A’wani Abdul Aziz; Nur Fazidah Asmuje@Asmuzi (Kolej PERMATA Insan, 2025)
Insan Junior Researcher International Conference & Innovation (iJURECON) 2025 : “STREAM for a Better Future/ editor : Ahmad Fuad Mohamad Amin, Nurul Shazwani Binti Mohamed, Rossidi Bin Usop, Abdel Rahman Ibrahim Suleiman Islieh Organised by Kolej PERMATA Insan 10-11 October 2025